Ability of azlocillin and tobramycin in combination to delay or prevent resistance development in Pseudomonas aeruginosa - Wu, Y L; Scott, E M; Po, A L; Tariq, V N (Journal of antimicrobial chemotherapy, 1999)
The ability of combinations of azlocillin and tobramycin to prevent or delay resistance development in eight Pseudomonas aeruginosa isolates from cystic fibrosis (CF) patients was studied using chequerboard titration and in-vitro serial subculture. No isolate had developed resistance to tobramycin after 12 treatments with the antibiotic combination. Azlocillin resistance had not developed in four isolates after 16 exposures, and was delayed in the other four isolates for at least eight exposures. Beta-lactamase production was responsible for azlocillin resistance in two isolates and occurred to a lesser extent in a third.